Application of coconut and pineapple probiotics on copepod (acartia sp.) / Ros Anizah Mi’ad, Norliza Gerunsin and Nurain Johar - Mi’ad, Ros Anizah; Gerunsin, Norliza; Johar, Nurain (Universiti Teknologi MARA, Sabah, 2025)
Copepod serves as a live food, supplementing essential amino acids and fatty acids into the aquatic larval organism. Nevertheless, the mass production of copepods remains unfeasible. A study was conducted at a fish hatchery in UiTM Mukah to investigate the effects of different probiotics on the proliferation rate of copepod Acartia sp. Three treatments were carried out during a 77-day feeding trial: a tank with no probiotic (T1), a tank with coconut-based probiotics (T2), and a tank with pineapple-based probiotics (T3). Yeast containing good bacteria (Saccharomyces cerevisiae) was used as feed to the copepods. The proliferation rate was measured by counting the number of copepods observed throughout the experimental period. Each tank was initially stocked with 10 copepods. T3 (pineapple probiotic) achieved the highest proliferation rate, with 222.67 ± 1.453 copepods, significantly outperforming the other treatments. T1 (no probiotic) exhibited the lowest proliferation rate, with only 43.33 ± 0.882 copepods, and was also significantly different from the other treatments. The results demonstrate that the use of pineapple juice as a probiotic significantly enhances copepod proliferation in a mass culture. Subsequently, this finding suggests a potential solution to the current challenges in the copepods production for aquatic hatcheries.